"Emile Guimet's Network for Research and Collecting Asian Objects, ca.1877-1918" - Chang, Ting (De Gruyter, 2018)
This article examines the early history of the first national museum in France devoted to the arts and religions of Asia, the Musée Guimet, created in 1879. Through extensive archival research in unpublished sources it is revealed that the founder Emile Guimet employed an international network of scholars, agents, and dealers to expand the collection of objects as well as to disseminate leading research in Asian studies. The close examination of multilingual documents ranging from personal and official correspondence to billings and inventories shows both the aleatory and planned development of a leading international centre of Asian collections and studies.